THE INFLUENCE OF COMPETITORS, MARKET SEGMENTATION, MARKETING STRATEGY, AND BRAND IMAGE ON CUSTOMER SATISFACTION AT HOTEL LUMINOR JEMURSARI SURABAYA - Rina Agustina; Taudikhul Afkar; Wira Yudha Alam (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the influence of competitors, market segmentation, marketing strategy, and brand image on customer satisfaction at Hotel Luminor Jemursari Surabaya. Using a quantitative approach and survey method, data were collected from 57 respondents through a structured questionnaire. Multiple linear regression analysis revealed that all four independent variables simultaneously have a significant effect on customer satisfaction, with an adjusted R² of 77.1%. Partially, competitors have a negative influence, while market segmentation, marketing strategy, and brand image show significant positive effects. These findings offer strategic implications for hotel management in enhancing customer loyalty through service differentiation and brand reinforcement.